2007
DOI: 10.1098/rstb.2007.2199
|View full text |Cite
|
Sign up to set email alerts
|

Trends in recent temperature and radial tree growth spanning 2000 years across northwest Eurasia

Abstract: This paper describes variability in trends of annual tree growth at several locations in the high latitudes of Eurasia, providing a wide regional comparison over a 2000-year period. The study focuses on the nature of local and widespread tree-growth responses to recent warming seen in instrumental observations, available in northern regions for periods ranging from decades to a century. Instrumental temperature data demonstrate differences in seasonal scale of Eurasian warming and the complexity and spatial di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(79 citation statements)
references
References 31 publications
1
76
1
1
Order By: Relevance
“…Earlier dendroclimatological studies have shown that there are large spatial differences in the seasonal temperature changes over the past 2000 years across northwestern Eurasia (Briffa et al, 2008). According to a study from the eastern flank of the northern Urals, there was a pronounced increase in summer temperatures at the end of the 19 th and beginning of the 20 th century that was remarkably different from reconstructions in northern Fennoscandia, where no such warming could be observed (Briffa, 1995).…”
Section: Introductionmentioning
confidence: 97%
“…Earlier dendroclimatological studies have shown that there are large spatial differences in the seasonal temperature changes over the past 2000 years across northwestern Eurasia (Briffa et al, 2008). According to a study from the eastern flank of the northern Urals, there was a pronounced increase in summer temperatures at the end of the 19 th and beginning of the 20 th century that was remarkably different from reconstructions in northern Fennoscandia, where no such warming could be observed (Briffa, 1995).…”
Section: Introductionmentioning
confidence: 97%
“…We have also utilized other versions of some records, either because they reach longer back in time or because newer versions of the records have become available. We have thus used the Avam-Taimyr regional tree-ring width chronology (Briffa et al, 2008) instead of the Taimyr tree-ring width chronology (Naurzbaev et al, 2002). The Avam-Taimyr record is a combination of the tree-ring width chronologies from Taimyr (Naurzbaev et al, 2002) and Bol'shoi Avam (Sidorova et al, 2007).…”
Section: Proxiesmentioning
confidence: 99%
“…All variables showed a normal distribution, except some precipitation variables which were log-transformed to achieve or improve the normal distribution. Pearson's correlation coefficients (r) were calculated for the relationships between the RWI chronology and different climatic factors: precipitation, temperature, snow depth, length of growing season (number of days with mean daily temperature over 5°C per year) (Briffa et al 2008) and the start date of the growing season. The start dates of the growing season during the period from 1952 to 2012 were calculated based on the equation developed by Pop et al (2000).…”
Section: Climate-growth Analysismentioning
confidence: 99%